ANALISIS POTENSI PENERIMAAN TUNGGAKAN PAJAK KENDARAAN BERMOTOR PADA KANTOR SISTEM ADMINISTRASI MANUNGGAL DIBAWAH SATU ATAP (SAMSAT) MAKASSAR - Andi Marlinah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
Motor vehicle tax revenue from year to year fluctuations, which at the beginning of the semester to second semester in 2007 increased by 7.89%, but in the first half of 2008 has decreased by 20.77% of tax revenue. This is due to the lack of public awareness of the obligation to pay taxes, lack of good service to the level of long queues and long enough or because the vehicle is lost or damaged but not yet reported. Level of realization of arrears of PKB (motorcycle) was 22.69% with the potential revenues that can be invoiced in arrears in the amount of Rp1.896.510.096. While the realization of arrears of CLA (car) of 53.26%, and the potential revenue arrears PKB (cars) in semesters to come to be collectible by Rp1.463.836.453,5.